Relação solo-relevo na subunidade morfoescultural de Nova Santa Rosa - PR - Danzer, Micheli (2015)
The understanding of the soil and of the reliev resulting from the concern with the environmental consequences of historical related to the use, coverage and interference in the dynamic evolution of systems and pedological. Describe the relations betwen soil and relief allows understand their spatial distribution and the action of the factors triggering or control their dynamics and evolution. The identification and description of the forms of reliev, the strands and of classes of soil associated constitute the basis for the interpretation and conservation of environments. This way, the objective of the research was to charaterize and understand the between the soils and the morphology of the strands by means of techniques and tools of geotecnologies. Hese, added to the comments and field inspections helped with the identification of types and forms of prominence and strands. As well as the delimitation and description of soil systems that integrate the morfoescultural subunit of New Santa Rosa, located in the west region of Parana. The abovementioned subunit, defined by Bade (2014) from the compartmentalisation of the Paraná Basin morfoescultural III, was selected and studied based on the proposal of taxonomy and classification of the embossment of Ross (1992). The data of steepness and hipsometria, forms of prominence and of the strands, the soil and geological structure, obtained by means of the thematic maps, were the main results. The study allowed, also, gather important information on the spatial organization of soil systems along the strands and thus, understanding their evolution in different scales of landscape units